PENGARUH MOTIVASI, PELAYANAN FISKUS DAN SANKSI PAJAK MELALUI KONDISI KEUANGAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Karma Karma (Inovasi, 2021)
The purpose of this study was to determine the effect of motivation, fiscal services and tax sanctions through financial conditions on individual taxpayer compliance, either partially or simultaneously. The research design used in the preparation of this research is quantitative associative causal with descriptive explanation. The method of analysis used is path analysis with a total sample size of 100 respondents and the sampling technique used is the random sampling technique. The results of hypothesis testing prove that work motivation has a significant effect on taxpayer compliance by 0.139. Fiskus services have a significant effect on taxpayer compliance by 0.178. Tax sanctions have a significant effect on taxpayer compliance with a coefficient value of 0.553. The results of the simultaneous analysis prove that motivation, tax authorities, tax sanctions and financial conditions have a significant effect with a determination coefficient of 0.950 or 95%, the rest is explained by other variables outside of this study. Meanwhile, the results of moderation analysis (through) prove that motivation, tax authorities and tax sanctions through financial conditions have a significant effect on taxpayer compliance.